Pengaruh Pemberian Jahe Terhadap Penurunan Morning Sickness Pada Ibu Hamil TM 1 - Zuanita Oktaviani Putri; Kamidah Kamidah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Pregnancy is a natural process. During pregnancy, a woman's body usually experiences many changes, including an increase in estrogen and progesterone levels, and the production of the Human Chronic Gonadotropin (HCG) hormone which is caused by stomach acidity, which triggers morning sickness. Nearly 50-90% of women who are pregnant experience nausea and vomiting in early pregnancy. So far, treatments have been carried out to relieve morning sickness by giving anti-nausea drugs and also vitamins. Apart from anti-nausea and vitamins, ginger is an alternative herbal treatment used to relieve nausea and vomiting. Ginger is considered to have many components and benefits that are considered to be able to inhibit Serotonin which can help relax muscles in the digestive tract. Objective: To determine the effect of giving ginger on reducing morning sickness in pregnant women TM 1. Methods: This study used a quasi-experimental research design that was one group pretest -posttest design of 20 respondents in the 1st trimester of pregnant women who experience morning sickness using accidental sampling technique. Results: The results of the study using the Wilcoxon test obtained a value of P = 0.000 (P <0.05). Conclusion: There is an effect of giving ginger on reducing morning sickness in first trimester pregnant women